1981
DOI: 10.1093/ije/10.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Varicose Veins: a Risk Factor for Atherosclerotic Disease in Middle-aged Men?

Abstract: The prevalence of varicose veins was higher among lower social subjects and was positively associated with a body-mass index, cigarette consumption and diastolic blood pressure. A detailed dietary survey in a subsample of the population showed a significantly higher total calory intake in men with varicose veins but no difference in the distribution of the various nutrients. During follow up for subsequent atherosclerotic disease (average 6.6 yrs), men with varicose veins were at a significantly higher risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
1
26
0
3
Order By: Relevance
“…19 20 Follow up of men with VV in the Framingham study indicated that VV may be a risk factor for intermittent claudication and, at least in the lower social class, for coronary heart disease. 19 A recent prospective Finish study showed that rapid progression in carotid atherosclerosis was predicted by prolonged standing at work, giving rise to the hypothesis that haemodynamic changes associated with standing at work may play a role in both venous and arterial vascular disease. 20 In line with Kroeger and colleagues, 3 but in contrast to our previous study, 1 we found that smoking may be associated with a low risk of VV, although RRs were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…19 20 Follow up of men with VV in the Framingham study indicated that VV may be a risk factor for intermittent claudication and, at least in the lower social class, for coronary heart disease. 19 A recent prospective Finish study showed that rapid progression in carotid atherosclerosis was predicted by prolonged standing at work, giving rise to the hypothesis that haemodynamic changes associated with standing at work may play a role in both venous and arterial vascular disease. 20 In line with Kroeger and colleagues, 3 but in contrast to our previous study, 1 we found that smoking may be associated with a low risk of VV, although RRs were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged standing (or sitting) has been shown to be associated with the incidence of varicose veins (19,21,56). Interestingly, varicose leg veins were in turn associated with a higher incidence of atherosclerotic diseases in several studies, but the researchers provided no specific biological explanation for this co-emergence of varicose veins with arteriosclerotic vascular diseases (19,20). According to our hemodynam-ic hypothesis, varicose veins could contribute to atherosclerosis through increased hydrostatic venous pooling during standing and therefore lead to a further reduction in plasma volume and result in arterial flow changes that, in turn, lead to atherogenic turbulence and shear stress changes on the arterial wall, as described in more detail earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical evidence for hemorheologic factors in the etiology of atherosclerosis comes from experimental and human pathology, but to our knowledge there are neither clinical nor epidemiologic studies addressing this issue directly. However, the Framingham study found varicose veins -a condition more common in people standing a lot -to be predictive of atherosclerotic cardiovascular disease, and this finding could not be explained by traditional risk factors (19)(20)(21). In this population-based prospective study, long-term standing at work was hypothesized as a potential risk factor for atherosclerosis because of the hemodynamic changes associated with prolonged standing.…”
mentioning
confidence: 99%
“…Различия распространенности варикозной бо лезни среди взрослых, выявленные в исследовани ях, очень высоки -от 2 до 56% среди мужчин и от 1 до 60% среди женщин [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Столь значи тельный разброс данных не может не вызывать во просы, и при первом взгляде на географию прове денных исследований может сложиться впечатле ние, что он обусловлен именно этническими разли чиями обследованного населения (см.…”
unclassified
“…таблицу). На пример, у коренного населения Африки частота ва рикозного расширения вен составляет 5-6% [12,40], в Новой Гвинее [11], на некоторых островах Тихого океана распространенность заболевания также низка [2], в арабских странах достигает 11,5% [26], в то время как в Европе доля лиц с поражением вен составляет десятки процентов от взрослого на селения [3,4,8,10,13,14,17,18,20,22,23,25,[27][28][29]. Роль этнического фактора в развитии варикоз ной болезни косвенно была подтверждена в иссле довании, проведенном на калифорнийском побере жье США, где проживают все основные расовые группы [24].…”
unclassified